2004
DOI: 10.1097/01.aog.0000137352.93110.15
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Correlation Between Maternal Weight and Second Trimester Circulating Cell-Free Fetal DNA Levels

Abstract: Fetal DNA levels are affected by maternal weight in the second trimester. A correction for this effect may be needed in larger-scale studies or for future clinical applications that measure cell-free fetal nucleic acids in maternal circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…Several studies have detected significant effects of storage, as a binary or continuous variable, on circulating cfDNA levels in plasma and serum. 14,15 Moreover, a suggestive gradient of −0.66 GE/mL per month of storage has been reported. 9 However, this study shows that the effects of storage on DNA are complex and might not be properly controlled for by assuming a linear association with length of storage.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have detected significant effects of storage, as a binary or continuous variable, on circulating cfDNA levels in plasma and serum. 14,15 Moreover, a suggestive gradient of −0.66 GE/mL per month of storage has been reported. 9 However, this study shows that the effects of storage on DNA are complex and might not be properly controlled for by assuming a linear association with length of storage.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, maternal cffDNA levels increase by 21% per week in the first trimester. 14 Maternal concentrations of cffDNA then rise rapidly during the last few weeks of normal pregnancies, 14,15 and again there appears to be an association with placental apoptosis. 16 The incidence of cells displaying condensed chromatin at term is double that during the first trimester, and trophoblastic nuclei are principally involved.…”
Section: Discussionmentioning
confidence: 98%
“…This was in contrast to the preliminary results of Wataganara et al, which showed a significant inverse correlation between cff DNA and maternal weight, after adjustment for gestational age. 24 In this retrospective study, maternal weight was expressed in pounds (lb). Alternatively, in our prospective study, we used the BMI as an international standard for obesity measurement, adjusting bodyweight for height (weight [kg]/height squared [m 2 ]), instead of maternal weight alone.…”
Section: Discussionmentioning
confidence: 99%